O adulto e sua subjetividade no contexto das relações de cuidado : um percurso pelas teorias de Donald Winnicott e Silvia Bleichmar - Mariana Rúbia Gonçalves dos Santos (2021)
This dissertation investigates the place given by the theories of Donald Winnicott and Silvia Bleichmar to the adult and the subjectivity of the adult involved in a care relationship with a child. Our working hypothesis, formulated from contact with theories developed by feminist authors such as Chodorow, Doane and Hodges, and Parker, proposes that the little attention given by a theory to the subjectivity of the adult and, in particular, its unconscious dimension would favor idealized and prescriptive theoretical constructions to this adult as well as the relationships and care tasks. In the Introduction of the dissertation, we question, from the historical contextualization, the naturalization and idealization that commonly permeate the representations of the adult caregiver and care relationships, seeking to demonstrate how the allocation of care tasks to women, as well as the association of her image with the ideal of a good mother, are configured as socio-historical constructions derived from the bourgeois political project, instituted throughout the 18th and 19th centuries. We also seek to list the theoretical, clinical and social consequences of defense and maintenance of a rigid framework for assigning care tasks with the child defined based on the sex-gender of the caregivers. In the first article that makes up this work carried out a critical review of the mother's place as a facilitating environment in Winnicott's theory. In it, after a brief characterization of the main tasks assigned to the mother-baby pair, we see tensions present in the way Winnicott conceived the capacity for care and justified the assignment of these tasks to mothers. The conclusion points to the presence of two currents of thought in Winnicott, one that tends to naturalize and idealize care, linking it to the mother and another that gives room for understanding care as associated with the desire and history of each individual. In the second article, we performed a bibliographic review of the place given by Silvia Bleichmar’s theory to adults and their subjectivity in the context of care relationships. Our analysis demonstrates that although the great attention given to the adult's subjectivity and unconscious has not guaranteed the elimination of the prescription of care functions based on gender of the caregivers in her theory, she allowed the author to build an approach able to offer important counterpoints to idealized theoretical representations of the adult in the care relationships.